Repeated Use of the Psychoactive Substance Ethylphenidate Impacts Neurochemistry and Reward Learning in Adolescent Male and Female Mice - Robins, Meridith T.; Blaine, Arryn T.; Ha, Jiwon E.; Brewster, Amy L.; van Rijn, Richard M. (Frontiers in Neuroscience, 2019)
Schedule II prescription psychostimulants, such as methylphenidate (MPH), can be misused as nootropic drugs, i.e. drugs that enhance focus and cognition. When users are unable to obtain these prescribed medications, they may seek out novel psychoactive substances (NPSs) that are not yet scheduled. An example of a NPS reportedly being abused is ethylphenidate (EPH), a close analog of MPH but with a higher preference for the dopamine transporter compared with the norepinephrine transporter. Therefore, based upon this pharmacological profile and user self-reports, we hypothesized that repeated EPH exposure in adolescent mice may be rewarding and alter cognition. Here, we report that repeated exposure to 15 mg/kg EPH decreased spatial cognitive performance as assessed by the Barnes maze spatial learning task in adolescent male C57Bl/6 mice; however, male mice did not show alterations in the expression of mature BDNF - a protein associated with increased cognitive function - in key brain regions. Acute EPH exposure induced hyperlocomotion at a high dose (15 mg/kg, i.p.), but not a low dose (5 mg/kg, i.p.). Interestingly, mice exhibited significant conditioned place preference at the low EPH dose, suggesting that even non-stimulating doses of EPH are rewarding. In both males and females, repeated EPH exposure increased expression of deltaFosB - a marker associated with increased risk of drug abuse - in the dorsal striatum, nucleus accumbens, and prefrontal cortex. Overall, our results suggest that repeated EPH use in adolescence is psychostimulatory, rewarding, increases crucial brain markers of reward-related behaviors, and may negatively impact spatial performance.